2000
DOI: 10.1046/j.1365-2257.2000.00314_22_6.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of massive transplacental haemorrhage by flow cytometry

Abstract: Flow cytometry has been shown to be a more accurate and sensitive method than the Kleihauer-Betke test for the measurement of feto-maternal haemorrhage in Rh(D) incompatibility. This report describes the successful use of flow cytometry to detect and monitor the management of a massive transplacental haemorrhage (105 ml) of fetal Rh(D) positive cells in a Rh(D) negative woman. The report highlights the accuracy and reproducibility of the test and the stability of a blood sample when transferred 596 kilometres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Flow cytometry, in particular with monoclonal anti‐D, is well recognised as being the most accurate and reproducible method for FMH volume quantitation 10 . ‐ 12 We also found this approach to be extremely practical over a large geographical area 13 …”
Section: Discussionmentioning
confidence: 84%
“…Flow cytometry, in particular with monoclonal anti‐D, is well recognised as being the most accurate and reproducible method for FMH volume quantitation 10 . ‐ 12 We also found this approach to be extremely practical over a large geographical area 13 …”
Section: Discussionmentioning
confidence: 84%
“…It is possible that antibody‐coated D+ cells could be undetected or less well detected by the direct method depending on the particular epitope specificity and binding characteristics of the monoclonal anti‐D used, as reported in the case of D‐mismatched transfusion 26 or in FMH 25 . In contrast, Fong et al 27 reported no difference in the percentage of fetal D+ cells detected or anti‐D dosage from either direct or indirect techniques. However, they did note a much reduced D+ cell MCF signal in the direct method, which could be explained by low antibody‐binding affinity, low antibody concentration, and/or a lower F:P ratio .…”
Section: Discussionmentioning
confidence: 98%
“…As there are at least nine times more RhD sites on RhD-positive red cells compared with weak D red cells (Jones et al, 1996;Wagner et al, 2000) a standard dose of 500 IU anti-D might be sufficient for up to 40 ml FMH. However, larger FMH than this does occur and we have previously described an unexpected massive transplacental haemorrhage of 105 ml (Fong et al, 2000). In white individuals it has been estimated that 0.2-1% exhibit weak D expression .…”
Section: Discussionmentioning
confidence: 80%
“…, 2000) a standard dose of 500 IU anti‐D might be sufficient for up to 40 ml FMH. However, larger FMH than this does occur and we have previously described an unexpected massive transplacental haemorrhage of 105 ml (Fong et al. , 2000).…”
Section: Discussionmentioning
confidence: 83%